Analysis of Pregnancy and Lactation-related Expressions in the Summary of Product Characteristics and Patient Information Leaflets of the Drugs Used for the Treatment of Nausea and Vomiting - AKICI, AHMET (GALENOS YAYINCILIK, 2021)
Objective: Concerns and limited data on drug use in pregnancy and lactation raise the importance of relevant information in summary of product characteristics (SmPC) and patient information leaflets (PIL). This study aimed to examine the consistency of the information related to pregnancy/ lactation periods in SmPCs/PILs of drugs used for the treatment of nausea/vomiting. Methods: Details of the statements regarding pregnancy and lactation periods included in the current SmPCs/PILs of a total of 118 preparations, 21 of which were original, belonging to 12 drugs with nausea/vomiting indication, were examined. SmPCs/PILs of the generic drugs was compared with that of the original drugs to identify any minor or major difference. Results: Any of SmPCs or PILs did not contain pregnancy indication or related posology information. Pregnancy was contraindicated in all tropisetron preparations

pregnancy in 38.5% and lactation in 46.2% of metoclopramide preparations

and lactation in 66.7% of dimenhydrinate preparations. It is stated that drug is passed in milk and placenta in 60.2% and 35.6% of SmPCs respectively. The presence of the expression regarding the placental passage showed inconsistency only among metoclopramide preparations. The presence of pregnancy and lactation in the cautions before use section of the PILs showed intra-drug variations for dimenhydrinate, metoclopramide, ondansetron, and domperidone. Except aprepitant, at least one major difference was detected between the SmPCs/PILs of original and generic preparations. Major differences were most commonly (15.0%) seen in the lactation section of the PILs. Conclusion: It was determined that presence of specific expressions that may be critical for clinical practice, like the management of nausea/vomiting in pregnancy, might differ in the informative documents of medicinal products. It is noteworthy that there is at least one major difference in the documents of six of the seven drugs and that the warnings/precautions in the SmPCs/PILs of the originals of the drugs vary considerably from those of the generics. These findings indicate the need for new approaches in terms of both standardization and usefulness in clinical practice when developing informative content in SmPCs/PILs.
Keywords: Pregnancy; nausea; vomiting; generic; summary of product characteristics; patient information leaflet; MILK-PRODUCTION; PLACENTAL-TRANSFER; DOMPERIDONE; METOCLOPRAMIDE; MEDICATIONS; GALACTOGOGUES; MALFORMATIONS; ONDANSETRON; MOTHERS; SAFETY